MODEL FAMILY CENTER APPROACH (FCA) UNTUK MENINGKATKAN KOMPETENSI IBU PRIMIPARA DALAM MENINGKATKAN BERAT BADAN BAYI - Wardani, Diadjeng Setya; Wardani, Arti; Indrawan, I Wayan Agung (Media Penelitian dan Pengembangan Kesehatan, 2025)
Good breastfeeding competence can help the baby get enough calories to increase the baby's weight. The Family-Center Approach (FCA) model is a method that emphasizes family support to assist mothers to increase breastfeeding competence in primiparous mothers who have no previous breastfeeding experience. This research aimed to analyze the effect of FCA on increasing the competence of primiparous mothers in increasing baby weight. This study used a quasy experiment with a pretest-posttest with a control group design on 34 respondents who were divided into 2 groups (17 respondents in the mother group with high breastfeeding competence and 17 respondents in the mother group with low breastfeeding competence). The sample in this study was primiparous mothers who had babies aged 0-6 months in the working area of ​​the Dinoyo Health Center, Malang City. The results from this research using the Wilcoxon Test followed by the Mann-Whitney Test showed p= 0.000 (0.000 < 0.05), this shows that the highest increase in baby weight was in the group of mothers with high breastfeeding competence (mean rank 25.3) compared to the group of mothers with low breastfeeding competence (mean rank 9.7). FCA can increase the competence of primiparous mothers in breastfeeding. This was accompanied by a higher increase in baby weight compared to the comparison group.